The utilisation of waste heat from exhaust gases after drying process in plate heat exchanger - Kapustenko, P. O.; Klemeš, Jiří Jaromír; Arsenyeva, O. P.; Fedorenko, O. Yu.; Kusakov, S. K.; Bukhkalo, S. I. (The Italian Association of Chemical Engineering, 2020)
In many industrial applications, a considerable amount of heat is wasted with off and flue gases of different compositions, carrying not only sensible heat but also latent heat of condensable gas contained in the outgoing gaseous mixture. It is especially crucial for waste heat recovery from exhaust gases in such processes as the drying of different materials. Based on the mathematical model published in a previous paper for the models of PHE channels corrugated field the mathematical model of the thermal and hydraulic performance of PHE assembled from commercially produced plates is developed. It accounts for processes at the main corrugated field and also in PHE collectors and channels distribution zones. The results of mathematical modelling are compared with data obtained on a pilot unit for utilisation of waste heat from gases coming after tobacco drying. The PHE type TS-6MFG produced by AlfaLaval is tested. The content of the air incoming air-steam mixture was 10 % at a temperature of 140 °C. The comparison of modelling results and tests data have shown good accuracy of prediction. It allowed recommending obtained correlations and developed a mathematical model for the design of plate heat exchangers in applications with heat utilisation from exhaust gases after drying processes in the industry.
Keywords: flue gases; outgoing gaseous mixture; mathematical model; hydraulic performance of PHE; air-steam mixture; plate heat exchangers